Trajectories of Woman Career. Notion of Career and Strategies of Succesful Career - Zdanevičius, Arnas (Sociologija. Mintis ir veiksmas, 2004)
The aim of the article is to analyze the notion of woman's career and the trajectories of the career. The article is based on a view of the career as a projection that social life and social structure draws in specific biographies. The trajectories of woman's career is thus understood as way to analyze the structural constraints, connected with the societal stereotypes, relations of power and configurations of identity. The article provides an analysis of 22 woman biographies. The article attempts to draw not only an image of „career's woman“ but to understand the societal conditions for pursuing proffesional goals.
Keywords: career; subjective and objective careers; career woman; positional career; vocational career; permanent career; flexible career; linear career; spiraling career